Dopamine D2/3 receptor availability in alcohol use disorder and individuals at high risk: Towards a dimensional approach. (5th June 2020) - Gleich, Tobias; Spitta, Gianna; Butler, Oisin; Zacharias, Kristin; Aydin, Semiha; Sebold, Miriam; Garbusow, Maria; Rapp, Michael; Schubert, Florian; Buchert, Ralph; Heinz, Andreas; Gallinat, Juergen
Abstract: Alcohol use disorder (AUD) is the most common substance use disorder worldwide. Although dopamine‐related findings were often observed in AUD, associated neurobiological mechanisms are still poorly understood. Therefore, in the present study, we investigate D2/3 receptor availability in healthy participants, participants at high risk (HR) to develop addiction (not diagnosed with AUD), and AUD patients in a detoxified stage, applying 18 F‐fallypride positron emission tomography ( 18 F‐PET). Specifically, D2/3 receptor availability was investigated in (1) 19 low‐risk (LR) controls, (2) 19 HR participants, and (3) 20 AUD patients after alcohol detoxification. Quality and severity of addiction were assessed with clinical questionnaires and (neuro)psychological tests. PET data were corrected for age of participants and smoking status. In the dorsal striatum, we observed significant reductions of D2/3 receptor availability in AUD patients compared with LR participants. Further, receptor availability in HR participants was observed to be intermediate between LR and AUD groups (linearly decreasing). Still, in direct comparison, no group difference was observed between LR and HR groups or between HR and AUD groups. Further, the score of the Alcohol Dependence Scale (ADS) was inversely correlated with D2/3 receptor availability in the combined sample. Thus, in line with a dimensional approach, striatal D2/3 receptor availability showed a linear decrease from LR participants to HR participants to AUD patients, which was paralleled by clinical measures. Our study shows that a core neurobiological feature in AUD seems to be detectable in an early, subclinical state, allowing more individualized alcohol prevention programs in the future. Abstract : Differences between Low Risk (LR), High Risk (HR) and alcohol use disorder (AUD) participants.